The Effect of Social Media Marketing on Purchase Decisions Moderated by Product Quality - Wikantari, Maria Assumpta (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2022)
The study aims to determine the effect of social media marketing on purchase decisions moderated by product quality at McDonald’s/ McD. This research is considered as causal effect research. The respondents are 100 consumers of McD obtained by incidental sampling technique. The results of the data analysis of this research are (1) there is a significant positive effect between social media marketing variables and purchasing decisions, (2) there is a significant positive effect between McD’s product quality variables and consumer purchasing decisions, and (3) there is also a significant positive effect between the purchasing decision variables and social media strengthened by the quality of McD’s products which are able to moderate the two variables.